(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
Liver diseases, ranging from hepatitis to cirrhosis, present complex challenges for healthcare systems globally. Nurses play a critical role in managing these conditions through patient education, monitoring, and holistic care. This article explores the specific responsibilities of nurses in liver disease management and highlights evidence-based practices to improve patient outcomes.